Review Of The Medical Record Document Storage System At UPT Puskesmas Karanganyar - Liss Dyah Dewi Arini; Warsi Maryati; Maulana Charisma Ardiansyah (International Journal of Medicine and Health, 2023)
UPT Karanganyar Health Center Karanganyar Regency is a type urban non-inpatient health centers, so they only serve outpatient care and emergency. Based on the results of the survey and introduction of researchers, at UPT Karanganyar Health Center found a medical record document missfile. The Missfile was due to a lack of non-RMIK officers in the filing department careful in returning medical record documents in place, and amount the medical record staff in the filing is inadequate. This research aims to find out the medical record document storage system at UPT Puskesmas Karanganyar.This type of research uses descriptive research methods, with approach. The subjects in this study were medical record filing officers. The object of this study is a medical record document storage system in UPT Karanganyar Health Center. This research instrument uses guidelines interviews and observations. Data processing by collecting, editing, and data presentation.The result of this research is based on record numbering system medical uses UNS (Unit Numbering System) with Family Numbering, for alignment using SNF (Straight Numerical Filling) and storage using centralization with personal folders. Factor the cause of the missfile is the inaccuracy of the clerk in returning the document medical records to the filing rack, the impact of the missfile is service delays and duplication of medical records efforts made namely socialization with color coding.The author suggests that a tracer should always be used when retrieval of medical record documents, so that they are stored again medical record documents faster, and avoid missfiles. It is necessary control by medical record officers when non medical record officers put DRM back on the shelf. Conduct HR recruitment with competence and qualifications from D3 Medical Records.